Post-COVID-19 laryngo-tracheal sequelae: a comprehensive study at a tertiary care centre - Karthik P.; Rupa Mehta; Ranganath T. G.; Ajoy K. Behra; Atul Jindal; Himanshi Grover (The Egyptian Journal of Otolaryngology)
Abstract Background The laryngo-tracheal framework is a complex structure responsible for several functions, including phonation, airway formation for breathing, and preventing aspiration. These functions rely on precise neurological and structural coordination. The COVID-19 pandemic primarily affected the lungs and upper respiratory tract, and the patients were classified into mild, moderate, and severe categories to determine appropriate management strategies, including home isolation and hospital admission. Mild cases typically underwent home isolation, while moderate-to-severe cases required hospitalization. Moderate cases often necessitated oxygen supplementation through various means such as oxygen masks, non-rebreather masks, and high-flow nasal cannula, while severe cases required mechanical support and emergency procedures like intubation, continuous positive airway pressure, and tracheostomy. These interventions, along with other factors like viral neuritis and comorbid illnesses, result in various laryngo-tracheal sequelae; in this study, we have tried to look for the laryngo-tracheal sequelae in post-COVID-19 patients. Methods A sample of 348 patients who were diagnosed with COVID-19 using reverse transcription polymerase chain reaction were identified retrospectively, and their demographics, comorbidities, intubation/tracheostomy, and management data were collected; then all the patients were subjected to video-laryngoscopy, and findings were noted and analysed. Type of study Retrospective cross-sectional observational study. Objectives Primary objective of the study was to assess the rates of laryngo-tracheal sequelae occurring in post-COVID-19 patients. Secondary objective was to assess the role of various factors along with COVID-19 that have led to the sequelae. Results The study population included 348 participants, with an age distribution ranging from 21 to over 60 years. Post-COVID-19 symptoms were seen in 22.7% of all the patients included out of which hoarseness of voice 32.9%, difficulty in breathing 24.05%, and other related symptoms such as cough 18.98%, foreign body sensation 8.8%, throat irritation 7.5%, throat pain 5.06%, throat dryness 1.2%, and difficulty in swallowing 1.2% of the patients. Majority of our patients had history of hospital admission which was predominant (87.1%) over home isolation (10.3%). Most common comorbidity was diabetes mellitus (DM) (62.4%) along with hypertension. The various findings were noted in 10.1% of total patients included in the study including vocal cord polyps 19.9%, vocal cord paresis 19.9%, vocal cord granulomas 8.5%, vocal nodule 5.7%, and chronic congestion of laryngeal inlet 17.1% of the patients. Significant associations were observed between sequelae and factors such as hospital admission, intubation and tracheostomy, duration of O2 support, and diabetes mellitus. Conclusions Laryngo-tracheal sequelae are commonly present and are persistent for months after recovery from COVID-19 in hospitalized and intubated/tracheostomized patients due to various factors related to the disease and its treatment.